solve y - 4x =1 and 6x -5y =9
Answers
Answered by
12
SOLUTION:-
Eliminate method;
Given, equation;
y -4x= 1...........(1)
6x -5y = 9........(2)
From equation (1), we get;
=) y- 4x =1
=) y= 1+4x.........(3)
So,
Putting the value of y in equation (2), we get;
=) 6x- 5y= 9
=) 6x- 5(1+4x) =9
=) 6x -5 -20x =9
=) -14x = 9 +5
=) -14x = 14
=) x= 14/-14
=) x= -1
&
Eliminate tha value of x in equation (3), we get;
=) y= 1+ 4x
=) y= 1+ 4(-1)
=) y= 1+(-4)
=) y= 1-4
=) y= -3
Hope it helps ☺️
Similar questions